The Masonry Techniques of a Historical Bridge in Hypokremnos (i̇çmeler) - Uygun Gençer, Funda; Turan, Mine; Hamamcıoğlu Turan, Mine (Middle East Technical University, 2017)
This study focuses on characteristics of a historical bridge in Içmeler, Urla, Izmir. Urla, a historical settlement on the west of Izmir, has been part of a commercial network between Karaburun, çesme and Anatolia throughout history. The aim is to understand the construction technique and material usage in Hypokremnos Bridge and identify a possible sequence of the original construction. The linear bridge was constructed by using masonry technique. It has three openings with various sizes and supported with rounded arches. The bridge wall is crowned with a road way making a crest at its center a inclined façade. This study is composed of four phases; documentation, analysis of construction technique and material usage, historical evaluation and restitution. In the first phase, by using Tgi3D Su Photoscan 2.13 and Trimble SketchUp 2013 software, three dimensional model was prepared. Visual analysis of construction technique and material usage was carried out and the mortar sample from the bridge was investigated in the conservation laboratory in the second phase. Three dimensional manual photogrammetric documentation of the historical bridge has provided the advantage of conceiving many constructional details. This condensed observation of constructional features supported with comparative study on historical bridges in Anatolia has revealed that the elements and composition of the studied bridge presents Roman characteristics, but the masonry techniques used recall those of Turkish period. The detailed data about structural system gathered from different locations of the bridge was used for the production of reconstitution of system detail. Reconstitution model of the bridge was produced by using reconstitution of system detail. To identify construction phases of the bridge, literature survey was carried out. According to structural elements and composition of the bridge, it is thought to be constructred in Roman Period, however, both the randomness in the composition of the rough cut lime stones used in the outer shells of the bridge wall, and lack of system in the form and color composition of the cut sand stones in the arches and the sea façade may be interpreted as an end result of a comprehensive repair on total reconstruction in the Turkish period.
Hypokremnos’taki (içmeler) Tarihi Bir Köprünün Yığma Yapım Teknikleri
Keywords: Historical bridges; Hypokremnos; Masonry techniques